Dentine Hypersensitivity: A cross-sectional study in Karachi - Afsa Mujahid, Samina Kanwal, Zehra Ahmed, Anum Nisar, Syeda Noor Israr, Raffat Aziz, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the awareness of dentinal hypersensitivity among the patients visiting dental outpatient department at KMDC hospital, Karachi. Methodology: The data for this cross-sectional study was collected from 361 patients visiting dental OPD of Karachi Medical and Dental College, Karachi. After informed consent, a close ended type questionnaire was filled and patients were examined for dentin hypersensitivity. The data obtained was analysed using SPSS version 22. Result: Out of total participants, 40% male and 21.5% female significantly respond to dentin hypersensitivity (p-value 0.001). Dentin hypersensitivity was higher in males than in females .40-50 age group was more commonly affected and cold stimuli was the most common aggravating and initiating factor found. In addition to it, Aggressive tooth brushing and grinding are the main etiological factors for dentin hypersensitivity. Practical implication: This study may help to clearly understand the prevalence and associated risk factors of dentine hypersensitivity to develop effective and appropriate treatment. Conclusion: It is necessary to organize public awareness programmes regarding adequate brushing technique, good oral hygiene, avoidance of abrasive as well as erosive agents and counselling the dietary habits to prevent dentin hypersensitivity. Keywords: Personal awareness, dentin hypersensitivity, hydrodynamic theory, public awareness, aetiology, erosion